Tastea 1.0 - tasting tea / Irina Mohd Akhir and Nina Farisha Isa - Mohd Akhir, Irina; Isa, Nina Farisha (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Free tea for everyone!. This was the main crowd puller of the day. An event rarely conducted, was specially conducted by HATSS just to create a chance for UiTM Pulau Pinang Branch community to taste and benefit from tea drinking. 'Special Tea Tasting Day' was held on the 22nd of November 2018 at Laman Perdana, UiTM Cawangan Pulau Pinang. It was an alternative platform to an online forum in communicating and distributing knowledge specifically about tea. Many tea related booths, activities and show slots were queued for all the time that day, especially Free Tea Tasting session, Tea Edu-tainment busking and clip shows, Tea Talk - Forum, tea related booth games and Tea Exhibition booths. Miss Mimi Salwani Che Din - a Dietetic & Food Service Officer and also one of the special forum speakers for the day claimed that "Tea is not my cup of tea", (2018). As a dietician in Seberang Jaya Hospital, she reasoned that with a claim, "Tea is beneficial to be consumed routinely if only the right way. However, tea is bad, if it is taken daily with high sugar condiment such as white sugar and condensed milk", (C. D., M, Salwani, 2018). It was a jaw opening moment but accepted by many of the forum participants.